Minat Remaja Desa Karangrejo Kecamatan Petanahan Kabupaten Kebumen Terhadap Olahraga Sepakbola - Puput Widodo; Suradi Suradi (Departement of Mathematics Education, 2023)
This study aims to determine the interest of the youth of Karangrejo Village, Petanahan District, Kebumen Regency in the sport of football. The population of this study was Karangrejo Village, Petanahan District, Kebumen Regency, while the sample used was a total of 100 children who met the school age criteria which were taken by proportional sampling. Retrieval of data using a questionnaire, with the instrument used in the form of a questionnaire. The score is obtained from the sum of the scores on the questionnaire which consists of 40 items. The method used is survey method and the data analysis technique is descriptive statistical analysis with percentages. The results showed that the interest of the youth of Karangrejo Village, Petanahan District, Kebumen Regency was mostly in the medium category. The breakdown was as follows: 8 children (8%) were included in the very high category, 20 children (20%) were included in the high category, 35 children (35%) included in the medium category, 23 students (23%) included in the low category, and 14 children (14%) included in the very low category.